N-alkynyl derivatives of 5-fluorouracil: susceptibility to palladium-mediated dealkylation and toxigenicity in cancer cell culture - Weiss, Jason T.; Fraser, Craig; Rubio-Ruiz, Belén; Myers, Samuel H.; Crispin, Richard; Dawson, John C.; Brunton, Valerie G.; Patton, E. Elizabeth; Carragher, Neil O.; Unciti-Broceta, Asier (Frontiers in Chemistry, 2014)
Palladium-activated prodrug therapy is an experimental therapeutic approach that relies on the unique chemical properties and biocompatibility of heterogeneous palladium catalysis to enable the spatially-controlled in vivo conversion of a biochemically-stable prodrug into its active form. This strategy, which would allow inducing local activation of systemically administered drug precursors by mediation of an implantable activating device made of Pd(0), has been proposed by our group as a way to reduce drug’s systemic toxicity while reaching therapeutic levels of the active drug in the affected tissue / organ. In the seminal study of such an approach, we reported that propargylation of the N1 position of 5-fluorouracil suppressed the drug’s cytotoxic properties, showed high stability in cell culture and facilitated the bioorthogonal restoration of the drug’s pharmacological activity in the presence of extracellular Pd(0)-functionalized resins. To provide additional insight on the properties of this system, we have investigated different N1-alkynyl derivatives of 5-fluorouracil and shown that the presence of substituents near the triple bond influence negatively on its sensitivity to palladium catalysis under biocompatible conditions. Comparative studies of the N1- versus the N3-propargyl derivatives of 5-fluorouracil revealed that masking each or both positions equally led to inactive derivatives (>200-fold reduction of cytotoxicity relative to the unmodified drug), whereas the depropargylation process occurred faster at the N1 position than at the N3, thus resulting in greater toxigenic properties in cancer cell culture.